Aktivitas Antidiabetes Jamur Lingzhi (Ganoderma lucidum) pada Tikus Putih Jantan - Dwi Ningsih; Endang Sri Rejeki; Dewi Ekowati (Fakultas Farmasi Universitas Setia Budi, 2009)
Diabetes mellitus is one of the degenerative diseases of concern to government and society, because the incidence of sufferers is increasing from year to year. Lingzhi (Ganoderma lucidum) mushroom is a traditional medicinal plant which one of the benefits to treat diabetes mellitus. This study aimed to identify and seek the most effective dose of lingzhi mushroom extract to decrease blood glucose levels in white male rats of wistar strain. Lingzhi mushroom extracted by maceration with ethanol 96% and infuse it with aquadest. The ethanol extract was tested on each group of test animals with a dose of 1.18 mg/200 g BW; 2:36 mg/200 g BW and 4.71 mg/200 g BW. Negative control group given CMC 1% and the positive control group was given glibenclamide (90 mg/200gBB). Aqueous extract obtained was tested after the optimal dose of ethanol extract. Antidiabetic effect is obtained by measuring blood glucose levels for 2-week with intervals measure every week, then performed statistical tests with two-way analysis of variance with a level of 95% followed Dunnett test. The results showed that the lingzhi mushroom has antidiabetic activity in male rats. Ethanol 96% extract of lingzhi mushroom (1.18 mg/200 g BW) most effectively to decrease blood glucose. Water extract at a dose equivalent to 1.18 mg/200gBB have equally strong effects with ethanol extracts.